Developing of English Vocabulary Material Pocket Book for Pharmacy Vocational School Maarif 5 Kotagajah - Sanusi, Taufik; Suhono, Suhono; Hidayatullah, Rizky; Sari, Yeasy Agustina; Hidayah, Yayuk (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research is motivated by the results of observations, that the learning process in English subjects at SMK Ma'arif 5 Kotagajah has so far been teacher-centered and currently the teaching and learning process is that the teacher only uses the lecture method and uses only limited learning media by teachers and schools. This research aims to describe the procedures for developing pocket books, determine the validity of developing pocket books, and determine the effectiveness of developing pocket books as an English language learning medium at SMK Ma'arif 5 Kotagajah. This research uses the Research and Development (R&D) method. This research uses a development model developed by Borg and Gall and the development model in this research uses a design from ADDIE. At the Development stage, this vocabulary pocket book was assessed for its suitability by material experts and media experts. The learning media validation results obtained a very valid category with a percentage of 92.2% by material experts and 91.4% by media experts. It can be concluded that research into the development of pocket books as a vocabulary learning medium is stated to be very strong when used as supporting teaching materials. Keywords: English Vocabulary Material, Pocket Book Pharmacy, Developing English Material